2010
DOI: 10.4103/0974-8237.65480
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative computer navigation guided cervical pedicle screw insertion in thirty-three complex cervical spine deformities

Abstract: Background:Cervical pedicle screw fixation is challenging due to the small osseous morphometrics and the close proximity of neurovascular elements. Computer navigation has been reported to improve the accuracy of pedicle screw placement. There are very few studies assessing its efficacy in the presence of deformity. Also cervical pedicle screw insertion in children has not been described before. We evaluated the safety and accuracy of Iso-C 3D-navigated pedicle screws in the deformed cervical spine.Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…18 , 19 However, recently developed computer navigation systems facilitate obtaining real-time 3-dimensional instrument/screw tip information in each step of screw placement. 20 Subsequently, further developments in technology have enhanced safety and contributed to refi nement of surgical techniques. 21 , 22 Besides computer navigation systems, several aiming tools including CT cutout techniques and specifi c navigation templates have been introduced to obtain accurate placement of pedicle screws in the cervical spine.…”
Section: Computer-assisted Screw Insertion and Other Aiming Toolsmentioning
confidence: 99%
“…18 , 19 However, recently developed computer navigation systems facilitate obtaining real-time 3-dimensional instrument/screw tip information in each step of screw placement. 20 Subsequently, further developments in technology have enhanced safety and contributed to refi nement of surgical techniques. 21 , 22 Besides computer navigation systems, several aiming tools including CT cutout techniques and specifi c navigation templates have been introduced to obtain accurate placement of pedicle screws in the cervical spine.…”
Section: Computer-assisted Screw Insertion and Other Aiming Toolsmentioning
confidence: 99%
“…In the recent past, 3-dimensional (3D) navigation has evolved to be an excellent tool and has shown promising results in overcoming the challenges associated with pedicle screw insertion. 9 - 17 However, the existing literature on the use of intraoperative O-arm-based 3D navigation, specifically for CPS insertion, is still sparse with small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Krammer et al instrumented 12 human anatomic specimens with 3.5-mm screws from C3-C7 and found a lower complication rate with CAS than with topographic landmarks and lamino-foramitomy 52) . Comparative studies have shown consistently better accuracy results with CAS [65][66][67][68] . The downside with the use of CAS is that it is expensive and that intraoperative tracer loosening and position change cause a drift of the navigation map, leading to the malpositioning of the screws.…”
Section: Technical Advances In the Placement Of Cpsmentioning
confidence: 88%